Autopsy Findings in Suicidal Hanging – A Cross Sectional Study Based on the Documentation of the Department of Forensic Medicine & Toxicology in a Tertiary Level Institution in Dhaka, Bangladesh (Mugda Medical College Journal, 2026)
A cross-sectional, descriptive study was carried out in the Department of Forensic Medicine & Toxicology of Shaheed Suhrawardy Medical College, Dhaka, Bangladesh, to determine the characteristics of the autopsy findings in suicidal hanging cases. A total of 157 cases with complete external and internal examination details were included in this study. Data was obtained from the inquest reports, chalan, and death certificates (for hospital deaths) between January and December of 2023. The mean age of victims was 29.9±7.8 years. Most of the victims belonged to the 21–30 years age-group (41.4%). A female predominance was observed (65%). Married (72%) were more affected than unmarried (28%). Most of them belonged to middle-class families (52.2%). Regarding occupation, most of them were students (39.5%), and homemakers (28.7%). The most commonly used ligature material was rope (44%), followed by dupatta (29%), sari (17%) and lungi (10%). Autopsy report revealed that the positions of the knots were found predominantly on the left side (58.6%), followed by the right side (29.3%) and the back of the neck (12.1%). Slip-type knots were more common (62%) compared to fixed knots (38%). Most of the ligature marks were located above the thyroid cartilage (89.8%). Grooving of the ligature mark was observed in 86%, while petechial hemorrhage was noted in 54.1% cases. Tongue bite was observed in 36.9% and subconjunctival hemorrhage was seen in 39.4% cases. Damage to the neck muscle fibers was identified in 78.3%, while damage to the cervical vertebrae were found in 15.9% cases. Regarding fractures, the thyroid cartilage was involved in 16% and the hyoid bone in 30% cases. Parchmentization was observed in 53.5% cases. The most common reported cause of suicidal hanging was familial disharmony (34%), followed by romantic/relationship distress (23%), academic pressure and examination failure (18%), financial crisis (17%), and depressive illness (8%). These findings play a decisive role in ascertaining the manner of death, especially if doubt exists over whether this was suicidal, accidental or homicide in nature and highlight the urgent need for targeted suicide prevention, including improved mental health care, public awareness, and support for at-risk individuals.Mugda Med Coll J. 2026; 9(1): 37-42